Improved sound absorption with 3D-printed micro-perforated sandwich structures - Peng-Fei Zhang; Zhong-Hua Li; Yu-Jun Zhou; Qi-Fei Zhang; Bin Liu; Fei Liu; Si-Chen Pei; Ke Shi; Pei-kang Bai (Journal of Materials Research and Technology)
The micro-perforated sandwich structure based on triply periodic minimal surfaces (TPMS) is a lightweight, high-strength and multi-functional structure, which integrates heat exchange, impact resistance, energy absorption, etc., and has been widely used in many fields such as aviation and aerospace. In order to improve the sound absorption performance of Micro-perforated plate Diamond sandwich structure (MPP-DSS) at low frequency, a microperforated sandwich-polyurethane composite structure based on TPMS was proposed. The microperforation sandwich and polyurethane composite structure was prepared by freeze-drying method by filling polyurethane sound absorbent material in MPP-DSS. The sound absorption theoretical model of TPMS microperforated sandwich and polyurethane composite structure was established by transfer matrix method. The sound absorption properties of microperforated sandwich structures before and after polyurethane filling were studied. The results show that the TPMS micro-perforated sandwich layer filled with polyurethane strong sound absorption material can broaden the relative sound absorption bandwidth in the middle and low frequency band, make the peak sound absorption frequency move to the low frequency direction of 294 Hz, and widen the relative sound absorption bandwidth by 23.86%. The sound absorption performance of the low frequency band is mainly determined by the TPMS micro-perforation resonance sound absorption structure, and the sound absorption performance of the higher frequency band is mainly determined by the polyurethane strong sound absorption material, which has certain reference significance for how to design the lightweight high-strength middle-low frequency broadband sound absorption structure.